An investigation into flow behavior and acoustic mechanisms at the trailing edge of an airfoil. (July 2016) - Jackson, Beren R; Dakka, Sam M
The aerodynamic and acoustic testing of a NACA0012 airfoil section was performed in an open wind tunnel, focusing on noise mechanisms at the trailing edge to identify and understand sources of noise production. The sound measurement profiles were captured by embedding microphones along the chord at various distances from the trailing edge and at different geometric angles of attack. The embedded microphones have successfully captured all noise sources due to aerodynamic flow over the NACA 0012 airfoil at the trailing edge, which included the following major peak frequencies: 44, 93, 166, and 332 Hz. The fundamental frequency of the model tested was identified by peak frequency (166 Hz). It appears that these frequencies do not deviate as the angle of attack is increased. The general trend is Strouhal numbers decrease as the flow moves downstream which indicates the amount of resonance (i.e. periodic, non-random vortices) decreases further downstream, which is to be expected given the onset of turbulence. Two bands of frequencies were identified. The frequency spectra between 1 and 3 kHz show a measure of far-field noise energy while frequency spectra in the range 3–10 kHz show near-field noise energy which is due to mechanisms associated with wake flow (separation).